2010
DOI: 10.1523/jneurosci.0141-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic and Vesicular Coexistence of VGLUT and VGAT in Selected Excitatory and Inhibitory Synapses

Abstract: The segregation between vesicular glutamate and GABA storage and release forms the molecular foundation between excitatory and inhibitory neurons and guarantees the precise function of neuronal networks. Using immunoisolation of synaptic vesicles, we now show that VGLUT2 and VGAT, and also VGLUT1 and VGLUT2, coexist in a sizeable pool of vesicles. VGAT immunoisolates transport glutamate in addition to GABA. Furthermore, VGLUT activity enhances uptake of GABA and monoamines. Postembedding immunogold double labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
136
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 48 publications
10
136
0
1
Order By: Relevance
“…Moreover, vesicles expressing the heterotransporters participate in the exo-endocytotic cycle (Fattorini et al, 2009). Similar observations have subsequently been reported in the hippocampus and cerebellum (Zander et al, 2010). Based on our understanding of the role of vesicular neurotransmitter transporters, the most likely interpretation of these results is that Glu and GABA might be co-released from this sub-population of nerve terminals (Fattorini et al, 2009).…”
Section: Introductionsupporting
confidence: 80%
“…Moreover, vesicles expressing the heterotransporters participate in the exo-endocytotic cycle (Fattorini et al, 2009). Similar observations have subsequently been reported in the hippocampus and cerebellum (Zander et al, 2010). Based on our understanding of the role of vesicular neurotransmitter transporters, the most likely interpretation of these results is that Glu and GABA might be co-released from this sub-population of nerve terminals (Fattorini et al, 2009).…”
Section: Introductionsupporting
confidence: 80%
“…Dual glutamate/GABA transmission at MF synapses is supported by the following evidence: (1) GAD and VIAAT are expressed in MFTs (Sloviter et al, 1996;Gutiérrez et al, 2003;Zander et al, 2010), (2) GABA is released from isolated MF synaptosomes (Gó mez-Lira et al, 2002), (3) GABAA receptors are expressed in the postsynaptic density facing GAD-immunopositive MFTs (Bergersen et al, 2003), and (4) IPSCs are detected upon extracellular stimulation in st. granulosum (Walker et al, 2001;Gutiérrez et al, 2003;Safiulina et al, 2006; but see Mori et al, 2004;Uchigashima et al, 2007;Toni et al, 2008). Our results appear consistent with some of these observations but do not support the conclusion that postsynaptic GABAA receptors are activated by GABA release at MFTs upon phasic activity.…”
Section: Discussionmentioning
confidence: 97%
“…Their axons-the mossy fibers (MFs)-convey a complex signal to their postsynaptic targets comprising both monosynaptic, glutamatergic excitation and disynaptic, GABAergic inhibition (McBain, 2008). In addition to glutamate, mossy fiber terminals (MFTs) have been shown to contain GABA (Sandler and Smith, 1991), the GABAsynthesizing enzyme glutamate decarboxylase (GAD; Sloviter et al, 1996), and the vesicular transporter VIAAT (vesicular inhibitory amino acid transporter; Zander et al, 2010). Mixed (glutamatergic and GABAergic), apparently monosynaptic responses are recorded in CA3 pyramidal neurons upon stimulation of the granule cell layer, suggesting the two neurotransmitters might be coreleased from MFTs (Walker et al, 2001;Safiulina et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of recent studies have demonstrated-both in developing systems as well in adult animals-that single neurons across different brain areas co-express GABA and glutamate (Gómez-Lira et al 2005;Danik et al 2005;Gritti et al 2006;Wouterlood et al 2008;Fattorini et al 2009;Zander et al 2010), these findings do not provide conclusive evidence for GABA and glutamate co-release. In this regard, recent evidence shows that dopaminergic neurons may also use glutamate as a neurotransmitter in the striatum (Descarries et al 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Axon terminals containing vGlut1 are characterized by a lower probability of glutamate release than those using vGlut2 (Fremeau et al 2001). A number of recent studies have reported co-expression of GABAergic and glutamatergic markers in adult animals, such as in a subpopulation of neurons in the basal forebrain (Gritti et al 2006), calretinin-positive neurons in the entorhinal cortex (Wouterlood et al 2008), mossy fiber terminals of the hippocampus (Sandler and Smith 1991;Zander et al 2010), basket cell terminals of the cerebellum (Zander et al 2010), as well as in layer V cortical terminals (Fattorini et al 2009). …”
Section: Introductionmentioning
confidence: 99%